Association between Sleep, Alzheimer’s, and Parkinson’s Disease - Sumire Matsumoto (MDPI AG, 2021)
The majority of neurodegenerative diseases are pathologically associated with protein misfolding and aggregation. Alzheimer’s disease (AD) is a type of dementia that slowly affects memory and cognitive function, and is characterized by the aggregation of the β-amyloid protein and tau neurofibrillary tangles in the brain. Parkinson’s disease (PD) is a movement disorder typically resulting in rigidity and tremor, which is pathologically linked to the aggregation of α-synuclein, particularly in dopaminergic neurons in the midbrain. Sleep disorders commonly occur in AD and PD patients, and it can precede the onset of these diseases. For example, cognitively normal older individuals who have highly fragmented sleep had a 1.5-fold increased risk of subsequently developing AD. This suggests that sleep abnormalities may be a potential biomarker of these diseases. In this review, we describe the alterations of sleep in AD and PD, and discuss their potential in the early diagnosis of these diseases. We further discuss whether sleep disturbance could be a target for the treatment of these diseases.